Topic and afterthought in spoken French: From sentence syntax to discourse construction. - Garrido, Joaquín (Círculo de Lingüística Aplicada a la Comunicación, 2013)
On the discourse level, structures and units are usually considered not to be based on grammatical functions and categories. Macrosyntax thus belongs to pragmatics, with units such as the utterance and its core. Instead of two levels, grammar and pragmatics, or two kinds of syntax, micro- and macrosyntax, a sentence syntactic structure is proposed that accounts for discourse phenomena such as topic and afterthought. Discourse itself is made up of discourse units, with sentences as their component units, organized by networks of discourse relations.
Keywords: discourse; pragmatics; topic; discourse relations